(untitled) (Journal Of Educational and Psychological Researches, 2024)
The current study aims to identify the level of productive thinking skills and their relationship to the habits of mind among science teachers in the primary stage. The descriptive approach was used, and a list of productive thinking skills was prepared. A scale of habits of mind was applied to a group of teachers to measure validity and reliability. The study participants were 42 teachers. The results were monitored and processed using statistical methods. The results showed that the degree of science teachers’ practice of productive thinking skills as a whole was average, with a mean of 3.38. The most commonly practiced productive thinking skills were those of fluency and flexibility. The least practiced productive thinking skill was the originality skill. Teachers’ practices of deduction, interpretation, expansion, and imagination skills were average. The degree of science teachers’ possession of habits of mind as a whole was high, whereas the average reached 4.20. The level of habits of mind was high in five dimensions, which were: persisting, speaking, questioning, gathering data through all senses, and applying past knowledge to new situations. It was average in three dimensions: managing impulsivity, thinking flexibly, and metacognition. The study recommended the necessity of striving to develop productive thinking skills among science teachers and at all educational